New taxa of the subfamily Cantharinae (Coleoptera: Cantharidae) from south-eastern Asia, with notes on other species III - Švihla, Vladimír (Zootaxa, 2011)
New taxa of the subfamily Cantharinae are described and illustrated: Taocantharis gen. nov. (type species: Islamocantharis businskae Wittmer, 1997), Themus (Telephorops) kubani sp. nov. (N Laos), T. (Tel.) micheli sp. nov. (N Laos), Lycocerus murzini sp. nov. (China: Sichuan), L. unguiformis sp. nov. (China: Sichuan), L. nigrosericeus sp. nov. (N Thailand), L. sipekorum sp. nov. (India: Arunachal Pradesh), L. dilatatus sp. nov. (China: Guizhou), L. pacholatkoi sp. nov. (C Laos), L. costipennis sp. nov. (S Vietnam), L. vita sp. nov. (N Laos), L. wolfgangi sp. nov. (China: Sichuan), L. putzi sp. nov. (China: Sichuan), L. rubroniger sp. nov. (N Laos), L. marginalis sp. nov. (China: Yunnan), L. nakladali sp. nov. (China: Yunnan), L. krausi sp. nov. (N Laos), L. verticalis sp. nov. (N Myanmar), Stenothemus prothemoides sp. nov. (China: Yunnan), S. hajeki sp. nov. (China: Yunnan), S. dinshuiensis sp. nov. (China: Sichuan), S. distortus sp. nov. (N Laos), S. kubani sp. nov. (China: Yunnan), S. yanmenensis sp. nov. (China: Yunnan), S. tamil sp. nov. (India: Tamil Nadu), S. honza sp. nov. (India: Mahārāshtra), Prothemus kubani sp. nov. (China: Yunnan) and P. blankae sp. nov. (China: Yunnan). Taiwanocantharis Wittmer, 1984 stat. nov. is raised to generic rank (from subgenus of Cantharis Linnaeus, 1758). New combinations are proposed: Taiwanocantharis drahuska (Švihla, 2004) comb. nov. (from Cordicantharis Švihla, 1999), T. chumbiensis (Champion, 1926) comb. nov., T. dedicata (Švihla, 2005) comb. nov., T. inthanonensis (Wittmer, 1997) comb. nov., T. kambaitiensis (Wittmer, 1989) comb. nov., T. malaisei (Wittmer, 1989) comb. nov., T. metallipennis (Wittmer, 1997) comb. nov., T. pallidithorax (Wittmer, 1984) comb. nov., T. quinquenotatithorax (Pic, 1914) comb. nov., T. seinghukuensis (Wittmer, 1989) comb. nov., T. satoi (Wittmer, 1997) comb. nov., T. shergaoensis (Wittmer, 1989) comb. nov., T. thibetana (Gorham, 1889) comb. nov., T. thibetanomima (Wittmer, 1997) comb. nov., T. tripunctata (Wittmer, 1984) comb. nov. (all from Cantharis) and Taocantharis businskae (Wittmer, 1997) comb. nov. (from Islamocantharis Wittmer & Magis, 1987). Key for species similar to Lycocerus nigrolineatus Pic, 1914 is provided and new data and/or illustrations are given for Lycocerus svatopluki Švihla, 2004, L. nigrolineatus Pic, 1914, Stenothemus jindrai Švihla, 2004, S. bourgeoisi Wittmer, 1974, S. quadratithorax (Pic, 1917), Prothemus opacipennis (Pic, 1906) and P. svihlai Wittmer, 1987.